Hanoi Old Quarter: Craft Streets, Architectural Heritage, and Socio-Economic-Cultural Characteristics - Tuan, Bui Van (Journal of Posthumanism, 2025)
Hanoi’s Old Quarter is perhaps one of the most famous tourist destinations in both Hanoi and Vietnam. For foreigners and many Vietnamese people, the Old Quarter often brings to mind vibrant commercial activities, distinctive street food, and unique architectural works. However, these are merely the visible aspects of a much deeper reality: in fact, the value of the Old Quarter goes far beyond that. Essentially, the Old Quarter is a rare heritage site in both Vietnam and the world, having existed continuously for over a thousand years. It serves as a 'living museum' of Hanoi - preserving the city's historical memories and distinctive cultural values - while consistently playing the role of a dynamic 'economic engine' of the capital throughout its long history. In this context, the article argues that, with its globally outstanding values, Hanoi’s Old Quarter - together with the Thăng Long Imperial Citadel - contributes to shaping the identity of a world-class urban heritage site: the Thăng Long - Hanoi city.